2019
DOI: 10.1001/jamafacial.2018.1176
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking Tobacco With Complications in Head and Neck Microvascular Reconstructive Surgery

Abstract: IMPORTANCE Smoking is a highly prevalent risk factor among patients with head and neck cancer. However, few studies have examined the association of this modifiable risk factor on postoperative outcomes following microvascular reconstruction of the head and neck.OBJECTIVE To analyze the risk associated with smoking in patients undergoing free flap surgery of the head and neck.DESIGN, SETTING, AND PARTICIPANTS In this retrospective, population, database study, the National Quality Improvement Program data sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 36 publications
6
59
1
1
Order By: Relevance
“…The overall complication rate in the current study was 22.7% for the entire cohort, which compares favorably with a 28.2% overall complication rate reported in a study of 2193 patients with HNC using NSQIP data from multiple institutions. 15 This study reported a wound complication rate of approximately 16.7% to 20.8% and a URTOR rate of approximately 18.0% to 24.8%, similar to the wound complication rate of 17.0% and URTOR rate of 15.2% reported in the current study. Another institutional series reported an overall complication rate of 32.4%, although it should be noted that the complications were reported using the Clavien-Dindo grading system and included blood transfusion as part of the complication rate.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The overall complication rate in the current study was 22.7% for the entire cohort, which compares favorably with a 28.2% overall complication rate reported in a study of 2193 patients with HNC using NSQIP data from multiple institutions. 15 This study reported a wound complication rate of approximately 16.7% to 20.8% and a URTOR rate of approximately 18.0% to 24.8%, similar to the wound complication rate of 17.0% and URTOR rate of 15.2% reported in the current study. Another institutional series reported an overall complication rate of 32.4%, although it should be noted that the complications were reported using the Clavien-Dindo grading system and included blood transfusion as part of the complication rate.…”
Section: Discussionsupporting
confidence: 88%
“…Although some series have shown that smoking is associated with higher rates of surgical and medical complications, 27,28 other studies regarding head and neck surgical resection and free-flap reconstruction have not found smoking to be a significant independent predictor of surgical complications. 15,29 Last, prior disease or receipt of RT were not found to significantly increase the risk of overall or wound complications on univariate analysis or in multivariate models, which other studies similarly have found. 30,31 Multivariate analysis of LOS demonstrated that only UADT surgery, compared with cutaneous surgery, was an independent predictor.…”
Section: Discussionmentioning
confidence: 54%
“…Two recent studies have studied the impact of age on reconstructive head and neck surgery. The first of these J ENT Care Otolaryngol Res is a retrospective study in which 132 cases were reviewed, two groups of patients older or younger than 80 years [53]. The second study had a prospective design with cases and controls, with an N = 14 in each branch differentiated by age: older or younger than 90 years [54].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Active smokers are more likely to experience postoperative total joint replacement infection, necessitating reoperation . Smokers also have a higher incidence of failure in cervical and lumbar surgeries, higher incidences of incision site disruption and reoperation in head and neck cancer surgery, and poorer outcomes in a variety of other surgical procedures.…”
Section: Prehabilitationmentioning
confidence: 99%